Inhibitory effect of nano Stolephorus insularis and calcium hydroxide on glucosyltransferase (GTF) activity of Lactobacillus aciophilus - Yuanita, Tamara; Juniarti, Devi Eka; Marbun, Tarsardo (Conservative Dentistry Journal, 2023)
Background: Dental caries is the most common multifactorial infectious disease worldwide which referes to the process of destruction tooth hard tissue caused by bacterial by-products in the form of acids through carbohydrate fermentation. Lactobacillus acidophilus is one of the main cariogenic bacteria that causes caries by forming biofilms with the help ofglucosyltransferase (GTF) enzymes. Calcium hydroxide has limited antibacterial effects. Nano brown anchovy contains fluor as the active compound which has the potential as an antibacterial alternative agent. Purpose: To explain the inhibition of the combination of nano Stolephorus insularis and calcium hydroxide on the activity of the glucosyltransferase enzyme of Lactobacillus acidophilus bacteria. Methods: This study used a combination of nano Stolephorus insularis 3.125% with calcium hydroxide as a treatment and aquades as a control. The GTF enzyme was obtained from the supernatant centrifuged by Lactobacillus acidophilus in BHIB. The activity of the GTF enzyme was considered by calculating the fructose levels using High Performance Liquid Chromatography (HPLC) in a certain formula.Results: Decreased levels of fructose was obtained in the treatment group. From the results of Mann- Whitney data analysis, there were significant difference in the study groups. Conclusion: the combination of nano Stolephorus insularis with calcium hydroxide is effective to inhibit the glucosyltransferase enzyme activity of Lactobacillus acidophilus bacteria.